Pemanfaatan Tomat dan Nanas dalam Pembuatan Velva Utilization of Tomato and Pineapple in the Manufacturing of Velva - Satriono, Satriono; Johan, Vonny Setiaries; Hamzah, Faizah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of the research was to obtain the amount of tomatoes puree and pineapple puree in making velva. This research used a Completely Randomized Design (CRD) experiment with four treatments and four replications followed by Duncan’s New Multiple Range Test (DNMRT) at level of 5%. The treatments in this research were TN1 (tomato puree 70%, pineapple puree 30%), TN2 (tomato puree 50%, pineapple puree 50%), TN3 (tomato puree 30%, pineapple puree 70%) and TN4 (tomato puree 10%, pineapple puree 90%). The result of analysis of variance showed that different percentase of tomato puree and pineapple puree in significantly affected the degrees of overrun, melting time, total dissolved solid, vitamin C and assessment sensory (descriptive and hedonic) of velva the best treatment this reseach was TN3 with overrun 22.65%, melting time 16.69 minutes, total dissolved solid 29.65°Brix, vitamin C 10.73 ml/100 g.The result of descriptive test assessment showed that the velva had orange color (3.30), tomato and penealple falvour (3.33), tomato and penealple taste (2.47), and soft texture (3.67). Overrall assessment of hedonic test on puple sweet potato velva was preferred by the panellist. Keywords: velva, tomato, pineapple